Eugenio Pacelli—Man and Pope - O'Shea, Paul Damian (Harvard theological review, 2013)
At the time of his death in October 1958, Pope Pius XII was remembered as a great and good man who had worked tirelessly for peace throughout his -nineteen-year pontificate. World leaders paid him fulsome tributes, and -accounts of his life and the details of his funeral were posted on the front pages of many of the world's leading newspapers and seen by hundreds of thousands on newsreels and television. Within the Catholic Church, Pius was the last of the great monarchical popes, a man who had lived his entire life within the framework of Vatican diplomacy, as an ambassador for two popes, secretary of state for one pope, and a detail-observant manager for close to two decades as pope himself. He was praised also for his support of new movements in the life of the church, notably a modern approach to the study of Scripture and the beginnings of significant reforms to the liturgy. There was, too, some relief that the stultification of the last years of the pope's life and fears of a new anti-Modernist campaign were over. The outpouring of grief at his passing was genuine, but there was a palpable sense that something had changed; an era was closing.